2021
DOI: 10.1016/j.toxcx.2021.100074
|View full text |Cite
|
Sign up to set email alerts
|

Chronic health effects and cost of snakebite

Abstract: The burden of disability among survivors and the socio-economic impact of snakebite have not been adequately researched. We reviewed original research articles, case reports and small case series relating to chronic physical, mental and psycho-social disability and economic burden of snakebite. Both physical and psychological health problems seem common in snakebite survivors and can lead to disability and loss of productivity. Chronic physical health effects, musculoskeletal disability being the commonest, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 75 publications
2
22
0
1
Order By: Relevance
“…In this vein, integrating THs into allopathic healthcare services offers opportunities for improving patient follow-up post-discharge in the outpatient setting. This is particularly relevant in the setting of snakebite envenoming, in which patients often struggle to afford prolonged hospital admissions ( Schioldann et al, 2018 ; Harrison et al, 2009 ; Steinhorst et al, 2021 ; Arias-Rodríguez and Gutiérrez, 2020 ; Brown, 2012 ) and in which long-term follow-up, especially with regard to disability and morbidity, is notoriously challenging ( Aglanu et al, 2022 ; Brenes-Chacon et al, 2020 ; Jayawardana et al, 2016 ; Kasturiratne et al, 2021 ). Many patients and THs see promise in therapies offered at the hospital, most notably antivenom ( Chuat et al, 2021 ; Vaiyapuri et al, 2013 ; Steinhorst et al, 2021 ; Schurer et al, 2022 ).…”
Section: The Role and Scope Of Traditional Healers In Snakebite Endem...mentioning
confidence: 99%
“…In this vein, integrating THs into allopathic healthcare services offers opportunities for improving patient follow-up post-discharge in the outpatient setting. This is particularly relevant in the setting of snakebite envenoming, in which patients often struggle to afford prolonged hospital admissions ( Schioldann et al, 2018 ; Harrison et al, 2009 ; Steinhorst et al, 2021 ; Arias-Rodríguez and Gutiérrez, 2020 ; Brown, 2012 ) and in which long-term follow-up, especially with regard to disability and morbidity, is notoriously challenging ( Aglanu et al, 2022 ; Brenes-Chacon et al, 2020 ; Jayawardana et al, 2016 ; Kasturiratne et al, 2021 ). Many patients and THs see promise in therapies offered at the hospital, most notably antivenom ( Chuat et al, 2021 ; Vaiyapuri et al, 2013 ; Steinhorst et al, 2021 ; Schurer et al, 2022 ).…”
Section: The Role and Scope Of Traditional Healers In Snakebite Endem...mentioning
confidence: 99%
“…15 El conocimiento de las características epidemiológicas de las mordeduras de serpientes, es decir, la incidencia, distribución geográfica, población en riesgo, las circunstancias de la mordedura y su gravedad ayudan a tomar medidas para mejorar su gestión. 16…”
Section: Caso Clínicounclassified
“…In particular, snake venoms, consisting of various types of proteins and small peptide cocktails, have been gaining significant attention as novel sources of drug discovery in recent years [ 10 , 11 , 12 ]. The main reason for understanding the compositions of snake venom is that snake bites are considered serious health and economic problems worldwide [ 13 , 14 , 15 , 16 ]. Annually, it is reported that more than 2 million snake envenomations occur globally, leading to a high mortality rate in Asia, Africa, and America [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%